2013
DOI: 10.3727/096368912x647144
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Transplantation of Differentiated Human Embryonic Stem Cells to Hemiparkinsonian Monkeys

Abstract: To explore stem cell therapy for Parkinson’s disease (PD), three adult rhesus monkeys were first rendered hemiparkinsonian by unilateral intracarotid 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) infusion. Five months postinfusion, they were given MRI-guided stereotaxic intrastriatal and intranigral injections of green fluorescent protein (GFP)-labeled cultures of dopaminergic neurons derived from human embryonic stem cells (DA-hES cells). The animals were immunosuppressed using daily oral cyclosporine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
(61 reference statements)
1
41
3
Order By: Relevance
“…However, these cell sources are allogenic and may incur immune rejection. In addition, the use of human embryos or fetal central nervous system tissue may give rise to ethical concerns when they are used in clinical practices for PD [14,15]. The generation of induced pluripotent stem cells (iPS cells) through somatic cell reprogramming provides great promise to patients with neurodegenerative diseases such as PD because the iPS cells can be generated from autologous cells and are able to overcome the barriers of allogenic cell transplantation [16e20].…”
Section: Introductionmentioning
confidence: 99%
“…However, these cell sources are allogenic and may incur immune rejection. In addition, the use of human embryos or fetal central nervous system tissue may give rise to ethical concerns when they are used in clinical practices for PD [14,15]. The generation of induced pluripotent stem cells (iPS cells) through somatic cell reprogramming provides great promise to patients with neurodegenerative diseases such as PD because the iPS cells can be generated from autologous cells and are able to overcome the barriers of allogenic cell transplantation [16e20].…”
Section: Introductionmentioning
confidence: 99%
“…Emborg and collaborators (2013) implanted iPSCs in the anterior and posterior parts of CdN; in the anterior, mid-and posterior parts of Put; and in SN (2.5-5 × 10 5 cells per site) of hemiparkinsonian rhesus monkeys 12 to 18 months following MPTP intoxication by intracarotid infusion (Emborg et al, 2013b). There was no obvious behavioral recovery and no PET change (data not shown) following transplantation.…”
Section: Impact Of the Immune Status Of The Host Brainmentioning
confidence: 99%
“…These recent studies suggest that immunosuppression can only be withdrawn in the autologous models (Emborg et al, 2013b;Morizane et al, 2013;Sundberg et al, 2013). Direct comparison of autograft and allografts in the lesioned NHP brain might ultimately confirm the efficacy and safety of autologous iPSC-derived or iDA cells.…”
Section: Impact Of the Immune Status Of The Host Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the immunomodulatory effects of MSC on microglial in coculture systems involving cell-cell interactions [15,17,18]. However, there are more obstacles and complex effects produced with cell transplantation in the CNS than in other parts of the body [19,20]. This study was initiated to determine the paracrine effects of MSC using MSC-conditioned medium (MSC-CM) in modulating microglial activities in vitro.…”
Section: Introductionmentioning
confidence: 99%